Wastes and biomass materials as sustainable-renewable energy resources for Jordan. (January 2017) - Al-Hamamre, Zayed; Saidan, Motasem; Hararah, Muhanned; Rawajfeh, Khaled; Alkhasawneh, Hussam E.; Al-Shannag, Mohammad
Abstract: An assessment of biomass resources potential in Jordan for power/heat generation and biogas production is presented in this paper. The investigation is based on five crucial requirements toward process sustainability and production cost. These requirements include biomass analysis and availability, conversion technologies, optimizing efficiency, reduction of environmental impact, and political decisions. All of these requirements collectively work in synergy toward commercial implementation of bioconversion technologies of biomass into energy. The information obtained in this study is expected to be useful for both decentralized and centralized wastes based energy planning by policymakers and industry developers, which can increase the biomass based renewable energy share to the energy mix. Direct biomass resources including agricultural residues, animal manure and municipal solid waste are considered in the analysis. Jordan produces more than 5.83 MT of wastes and residues annually, where 42% of which are estimated as available sources for energy generation and biogas production. The corresponding annual biogas and power potential is 313.14 MCM and 847.39 GWh, respectively. The produced biogas could replace almost 23.64% of Jordan primary energy consumed in the year 2012 in the form of natural gas (656 toe). Amongst all wastes and residues, municipal solid waste generated in the middle region of Jordan has the highest potential for biogas and power generation at 24.26%. This is followed by poultry manure with 18.58% and olive residues with 15.1%. The potential of the other wastes and residues is estimated at 42.06%.